Teo Estetis Cerita ?akuntala Dalam Teks ?diparwa - Ida Bagus Subrahmaniam Saitya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2021)
Theo aesthetic of the ?akuntala story in the ?diparwa text contains elements of Satyam, Siwam, and Sundaram. The Satyam element in ?akuntala's story is when Bagawan Ka?wa sincerely nurtures Sakuntala from infancy to adulthood, even though ?akuntala is not the biological child of Bagawan Ka?wa. In addition, the Satyam element is also seen when King Du?wanta acknowledged the truth that ?akuntala was his wife and Sarwadamana was his son. The Siwam element in the ceritaakuntala story is seen by the mention of Dewat?s, namely Sanghyang ?tma Sanghyang ?ditya (S?rya), Sangyang Candra, Sanghyang Angin (Bayu), Sanghyang Agni, Sanghyang Ak???, Sanghyang P?thiwi, Sanghyang Toya, and Sanghyang Yama. The Sundaram element in the ?akuntala story depicts the beauty of Bagawan Ka?wa's hermitage with a peaceful atmosphere. In addition, the Sundaram element can also be seen in the mabebas tradition in Bali, ?diparwa because it is in the form of parwa generally sung in palawakya, so the mabdeka tradition in Bali consists of wirama, wiraga, and wirasa when palawakya gives beauty to connoisseurs of Balinese art.